Herramientas tecnológicas educativas en el proceso de enseñanza-aprendizaje inicial de la U.E. “Alfredo Pérez Guerrero”. - Chicaiza, Verónica L. (2022)
The purpose of this research is to expose the benefits of including technological tools in initial education focused on enhancing the teaching-learning process, based on the professional and empirical knowledge of teachers at this level. The problem lies in the lack of a full approach to digital resources in education, attributed to ignorance and poor pedagogical training in their use. To analyze the phenomenon in question, a theoretical data collection methodology has been proposed through documentary research, complemented by obtaining specific information on the medium studied through teacher surveys; and later, the compilation of results, their evaluation and processing confirmed the formulated hypothesis. With the information collected, the relevance of including ICTs in the children's curricular framework is verified, hand in hand with a nurtured knowledge in digital matters, both theoretical and practical, to make the most of the benefits that these resources grant to the initial educational environment, emphasizing in the need for an equitable investment between the provision of technological tools and teacher training in their use. The statistical evaluation of the collected data shows an error below the acceptable threshold of 5%, approving the proposed hypothesis. In conclusion, technological tools, with a didactic and playful approach, can enhance the teachinglearning process at the initial educational level of the Alfredo Pérez Guerrero Educational Unit. empowering this document as an important foundation for future related research.